Frequency of Mycoplasma pneumoniae among atypical pneumonia of childhood - Oğuz, Fatma; Ünüvar, Emin; Aydın, Derya; Yılmaz, Kutluhan; Sıdal, Müjgan (The Turkish Journal of Pediatrics, 2002)
We aimed to investigate the frequency of Mycoplasma pneumoniae among atypical pneumonia of childhood that is acquired from the community and to determine a practical approach to the diagnosis of these patients. In this prospective study, 55 patients (31 male and 24 female) with atypical pneumonia were investigated with conventional laboratory and radiological methods as well as culture and polymerase chain reaction (PCR) on throat swab. In addition, serum of the patients was tested for M. pneumoniae specific IgM. The patients were reevaluated clinically at 3-5 days and 3-4 weeks and serologically at 3-4 weeks. The data on patients with M. pneumoniae pneumonia were compared with the other patients with atypical pneumonia and controls. All patients were treated with macrolide antibiotics. The mean age of the patients was 7.8±2.9 years. The frequency of M. pneumoniae by this method was 34.5%. Neither clinical, laboratory, or epidemiological data nor response to macrolide antibiotics was useful in detecting the etiology of atypical pneumonia. Diagnostic sensitivity and specificity of IgM+IgG antibodies plus PCR on throat swab were estimated as 100%. M. pneumoniae was an important microorganism in the etiology of atypical pneumonia of childhood in our community. In order to prevent loss of time with beta-lactamase antibiotics, which are usually started in severe pneumonia, serologic tests and PCR must be done during the initial evaluation of the patient for the reliable diagnosis of M. pneumoniae, which will increase the chance of early and appropriate therapy.